Tumor necrosis factor-α and muscle wasting: a cellular perspective - Li Yi-Ping; Reid Michael B (Respiratory Research, 2001)
Abstract Tumor necrosis factor-α (TNF-α) is a polypeptide cytokine that has been associated with muscle wasting and weakness in inflammatory disease. Despite its potential importance in muscle pathology, the direct effects of TNF-α on skeletal muscle have remained undefined until recently. Studies of cultured muscle cells indicate that TNF-α disrupts the differentiation process and can promote catabolism in mature cells. The latter response appears to be mediated by reactive oxygen species and nuclear factor-κB which upregulate ubiquitin/proteasome activity. This commentary outlines our current understanding of TNF-α effects on skeletal muscle and the mechanism of TNF-α action.